The ash dispersion over Europe during the Eyjafjallajökull eruption e Comparison of CMAQ simulations to remote sensing and air-borne in-situ observations - Matthias, Volker; Aulinger, Armin; Bieser, Johannes; Cuesta, Juan; Geyer, Beate; Langmann, Bärbel; Serikov, Ilya; Mattis, Ina; Minikin, Andreas; Mona, Lucia; Quante, Markus; Schumann, Ulrich; et al. (Atmospheric Environment, 2012)
The dispersion of volcanic ash over Europe after the outbreak of the Eyjafjallajökull on Iceland on 14 April 2010 has been simulated with a conventional three-dimensional Eulerian chemistry transport model system, the Community Multiscale Air Quality (CMAQ) model. Four different emission scenarios representing the lower and upper bounds of the emission height and intensity were considered. The atmospheric ash concentrations turned out to be highly variable in time and space. The model results were compared to three different kinds of observations: Aeronet aerosol optical depth (AOD) measurements, Earlinet aerosol extinction profiles and in-situ observations of the ash concentration by means of optical particle counters aboard the DLR Falcon aircraft. The model was able to reproduce observed AOD values and atmospheric ash concentrations. Best agreement was achieved for lower emission heights and a fraction of 2% transportable ash in the total volcanic emissions. The complex vertical structure of the volcanic ash layers in the free troposphere could not be simulated. Compared to the observations, the model tends to show vertically more extended, homogeneous aerosol layers. This is caused by a poor vertical resolution of the model at higher altitudes and a lack of information about the vertical distribution of the volcanic emissions. Only a combination of quickly available observations of the volcanic ash cloud and atmospheric transport models can give a comprehensive picture of ash concentrations in the atmosphere.